Influence of spiritual intelligence, age and tenure on work performance of nurses in selected hospitals, Peninsular Malaysia - Abdul Rani, Anita (2015)
Spiritual Intelligence has been discussed through out many years. Previous reseach studies on it have been explored extensively in the context of human development, organization, education and health. The importance of spiritual intelligence are found in the healthcare service as nurses deal with stressful environment that can effect their performance. Spiritual intelligence as believed can give a positive attitude and productive in work will lead to good quality of care. However, there are few studies on it in examining the effect of spiritual intelligence with nurse’s work performance especially in Malaysia. Applying Tischler’s model (2002) and a great support from Theory of Work Performance (Blumberg & Pringle, 1982), this study attempts to identify important item among domains in spiritual intelligence from nurse’s perceptions, to determine the relationship of nurses’ spiritual intelligence and their work performance, to examine demographic factors as a moderator between spiritual intelligence and work performance and to test the best model of Nurse’s Work Performance (NWP). The research empirically validate the hypothesized model of the influence of spiritual intelligence towards work performance among nurses in the selected hospitals in the East Coast of Malaysia. By employing cluster sampling procedure, 505 nurses answered a set of questionnaire that consists of Integrated Spiritual Intelligence Scale (Amram & Dryer, 2009) and Six Dimension Scale (Schwirian, 1978). The hypothesized model was analysed using structural equation modelling (SEM) with AMOS software version 18.0 in order to test the relationships on the impact of spiritual intelligence on work performance. In addition, this study also investigated the moderating effect of age, tenure and work place location on the model. The findings from the modelling analysis revealed the fit statistics of the hypothesised model i.e. p-value = 0.000, normed chisquare=3.999, CFI=0.972, TLI=0.963, GFI=0.939 and RMSEA=0.077. This showed that the model is valid and acceptable. In addition, the findings showed that the moderating factor of nurse’s age and hoslital’s location is not significant and it could be concluded that the model is applicable to all nurse’s age and all hospitals involved in this study. The findings also suggested that the spiritual intelligence can give a positive effect on work performance. The research makes several theoretical contributions and also paves the way forward to empower spiritual intelligence in nursing schools and training centres to enhance nurse’s work performance especially in East Coast of Malaysia.